Death is but a dream : finding hope and meaning at life's end - Kerr, Christopher, M.D; Mardorossian, Carine M., 1966- (Avery, an imprint of Penguin Random House, 2020)
"The first book to explore the meaningful dreams and visions that bring comfort as death nears"--